PENGARUH SUHU DAN LAMA WAKTU KONTAK OZONE TERHADAP DAYA TETAS TELUR IKAN LELE DUMBO (Clarias gariepinus) - Hengga, Everd (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2021)
This study is entitled Effect of Temperature and ozone Contact time on The Eggs Hatching Rate of African Catfish(Clarias gariepinus) This study aims to determine the level of temperature and ozone contact time that produces ozone concentration levels highest percentage of eggs hatching. Catfish (Clarias gariepinus) is one of the ten main aquaculture commodities in Indonesia, which is currently experiencing a decline in hatching eggs. The experimental design was in the research factorial with a Completely Randomized Design(CRD), consisting of two factors temperature (25 0C and 30 0C ) and contact time ozone (2, 4, 6 dan 8 minuts) with 3 replications. The data were analyzed using anova two factore. The result showed that combination of temperature of 25 0C with 8 minuts contact time indicatet that average level of the highest concentrations of ozone in water of 0,083 mgO3 / l was highly significant (p<0,01) but this treatment it was significattly (p<0,05) lowered hatchability of eggs 46,67 %. As for temperature of 30 0C that combination treatment with ozone contact time of 8 minutes showed the concetrations ozone in the water level of 0,075 mgO3 / l was highly significant ( p < 0,01 ) highest eggs hatching (85,55 % ). The use of ozone in cobination with certain temperature and ozone contact time is only effective for the hatchability of eggs a temparature of 30 0C with ozone contact time of 8 minutes.